What Makes Effective Teaching in the 21st Century - Selli Hernawati S. (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Life and technology have developed from time to time. Aa consequences, they influence the education in the world. Technology has important role in educational program especially in the 21st century. It could be the big question today: what impact does technology give in the teaching and learning process in the classroom today? Chai(2005) makes the claims that a teacher has the opportunity toteach less, learn more. She argues that teaching is not just delivering knowledge. Teaching is about communicating: When I teach,I communicate with my students and I encourage them to communicate with me. I want to know their opinion about things, their hopes and fears, how they feel and how they reach to some situations. It is clear that the main factor in education is a teacher, beacuse a teacher plays an important role in learning process. Without teacher, the world will be lost. Teachers are facing more complex and difficult challenges of their works, for examples: an increasing diversity of students and parents, higher demands of education quality, the higher standard of teaching and learning process and outcomes, etc. Therefore, compared to the previous era, a professional teacher today should have wide range of teacher competencies, such as teaching and managing class effectively; building, developing, and managing the relationship with students and school community; using technology for more effective communication and instruction.Thus, creating a comfortable classroom for students is important for 21st century teaching.